P-197 Identification of a Homozygous Mutation in the ZBTB24 Gene in a Patient with Very Early Onset Inflammatory Bowel Disease. (March 2016) - Conrad, Maire; Dawany, Noor; Sullivan, Kathleen; Devoto, Marcella; Kelsen, Judith
Abstract : Background: Very early onset inflammatory bowel disease (VEO-IBD) occurs in children less than 5 years old and is frequently characterized by a more severe disease course than older onset IBD. The etiology likely includes a significant genetic contribution, particularly genes associated with immunodeficiency. The increased utilization of whole exome sequencing (WES) has identified several rare and novel variants in immune pathways that are associated with this phenotype. Methods: A 17-month-old boy with a family history of consanguinity and Crohn disease in his maternal grandmother initially presented with poor growth, recurrent fever, constipation, and intermittent blood in his stool. He was discovered to have a recurrent perianal fistula. Colonoscopy revealed multiple ulcerations in the distal 10cm of his colon and rectum. He was treated with azathioprine, corticosteroids, mesalamine enemas, and metronidazole and had resolution of his symptoms and fistula within 6 months. He developed serious infections as well, including multiple episodes of febrile pneumonia requiring hospitalization and IV antibiotics. Additionally he had 2 episodes of acute otitis media but no sinusitis or cellulitis. His growth remained poor. His physical exam was notable for hypertelorism, epicanthal folds, low set posteriorly rotated ears, and developmental delay. Results: Immune work up revealed combined immunodeficiency including total hypogammaglobulinemia, decreased production and maturation of B cells, decreased NK cells, and poor titer response to vaccines. WES detected a potential causative homozygous frameshift mutation, c.1492-1493delCA: p.Q498VfsX15, in ZBTB24, which is involved in B cell differentiation. The subject's mother and father are heterozygous for the same mutation. Homozygous and compound heterozygous mutations of ZBTB24 have been described in patients with immunodeficiency, centromeric instability, and facial anomalies syndrome type 2 (ICF2, OMIM 614069). Karyotype to confirm this diagnosis was performed. Conclusions: Underlying immunodeficiencies can present with phenotypic characteristics of VEO-IBD. Here whole exome sequencing together with immunophenotyping detected a novel variant in a known immunodeficiency gene presenting as recurrent pneumonia and inflammatory bowel disease.